EPINEPHRINE AND DEXAMETHASONE AS ADJUVANTS IN UPPER EXTREMITY PERIPHERAL NERVE BLOCKS IN PEDIATRIC PATIENTS - Ljubica Mikjunovikj-Derebanova; Andrijan Kartalov; Biljana Kuzmanovska; Ljupcho Donev; Albert Lleshi; Marija Toleska; Aleksandar Dimitrovski; Vasko Demjanski (Macedonian Academy of Sciences and Arts, 2021)
ABSTRACT Introduction: Regional anesthesia in children in recent years has been accepted worldwide. The increased interest in it is partly due to the use of ultrasonography which provides confidence and accuracy to the anesthesiologic team. Adjuvants are used to extend the duration of the sensory and motor blocking, limiting the cumulative dose of local anesthetics. The use of adjuvants in peripheral nerve blocks in the pediatric population is still under research. Aim: To observe the effect of epinephrine and dexamethasone as adjuvants to local anesthetics in peripheral upper extremity nerve blocks in pediatric patients. Materials and methods: The study included 63 patients, aged group 4-14 years, admitted to the University Clinic of Pediatric Surgery for surgical treatment of upper limb fractures in the period of January 2020 until March 2021. Patients were randomized into three groups, and all patients in the groups received analgo-sedation prior to peripheral nerve block. Patients in group 1 (21 patients) received supraclavicular, or interscalene block with 2 ml lidocaine 2% and bupivacaine 0.25% (max 2mg/kg) with a total volume of 0.5ml/kg. In group 2, the patients (21) received 25 μg of epinephrine in 2 ml of 2% solution of lidocaine and 0.25% bupivacaine (max 2 mg/kg) with a total volume of 0.5 ml/kg, and in group 3, the patients (21) received 2% lidocaine 2ml and 0.25% bupivacaine (max 2mg/kg) in combination with 2mg dexamethasone with a total volume of 0.5ml/kg. Results: Results showed that in patients in group 1, the average duration of the sensory block was 7 hours, while the duration of the motor block was 5 hours and 30 minutes. In group 2 (epinephrine), the durations of both sensory and motor block were prolonged for about 30 minutes on average compared to the first group. In group 3 (dexamethasone) the duration of the sensory and motor block was significantly longer compared with the first two groups (p<0.0001). Conclusion: Epinephrine and dexamethasone prolong the duration of action of local anesthetics in pe- ripheral nerve blocks of the upper extremity in pediatric patients and thus reduce the need for analgesics in the postoperative period.
Keywords: epinephrine; dexamethasone; adjuvants; plexus brachialis blocks; pediatric patients